Real Estate Credit and Liquidity Risk with Ownership Structure as Moderating Variables in Banking Companies Listed on The Indonesia Stock Exchange - Muhammad Madyan; Ilham Ramadhani; Rayindha Galuh Setyowati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
The purpose of this study is to investigate the effect of real estate credit on liquidity risk. This study also looked at the role of government ownership and foreign ownership in moderating the effect of real estate credit on bank liquidity risk. There are 43 banking companies listed on the Indonesia Stock Exchange for the 2014-2018 period used as samples. This study used a multiple linear regression model with the Ordinary Least Square (OLS) estimation method and robustness tests using the Maximum Likelihood (MLE) estimation method. The results of this study concluded that real estate credit has a significant positive effect on liquidity risk. Government ownership strengthens the positive effect of real estate credit on liquidity risk, while foreign ownership weakens the positive effect of real estate credit on liquidity risk.